A CFD study of swirl effect on hydrodynamics in a gas-liquid bubbly flow reactor - Ariny, Demong; Khairuddin, Sanaullah; Afrasyab, Khan (Asian Research Publishing Network (ARPN), 2017)
Gas liquid bubbly flow reactors are used in chemical and bioprocess industries to enhance the mass transfer between the gas and liquid phases. In bubbly flow reactors, the mass transfer is most important parameter, which affects the product conversion and reactor performance. Mass transfer can be enhanced by achieving more efficient mixing. One such method is the application of rotation or swirl to the gas liquid mixture. Commercial code, Ansys Fluent 14.0 has been used to simulate the phenomenon prevailing in the bubbly reactors with conventional gas injection as well as rotating bottom plate through which the gas is introduced into the column. An attempt has been made to assess the effect of gas injection and swirl bubbly flow, gas void fraction and shear stress by the use of CFD Code. The results of the investigation showed that the gas void fraction increased with increasing in air gas rate for both conventional and swirl gas injection